(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Colorectal carcinoma (CRC) in childhood is extremely rare, usually diagnosed at an advanced stage, and often has a poor prognosis. The disease in those younger than 20 years of age has an annual incidence of 1 case per million individuals worldwide. Case report: A 14-year-old female child underwent a left transverse and left descending colectomy for infiltrating adenocarcinoma of the descending colon, proven by the histopathology of the resected sample. Before that, the patient presented with abdominal pain, more on the left, and a history of chronic constipation. She had no history of ulcerative colitis or a family history of carcinoma of the colon or colonic polyposis. The tumor was MMR protein proficient and microsatellite stable on immunohistochemistry (IHC). Her serum Ca-19.9 was markedly raised, and pre-operative colonoscopy was also compatible with colonic growth. After surgery, a whole-body 18F-FDG PET-CT baseline scan and a post-chemotherapeutic follow-up scan after 3 months were done, revealing a good prognosis for the patient. Conclusion: Though CRC in childhood is an aggressive neoplasm with a poor prognosis, the recent case showed a good prognosis due to early diagnosis, correct treatment, and follow-up. The case also highlighted the usefulness of the 18F-FDG PET-CT scan. A PET-CT scan provides anatomic, morphologic, and metabolic information about the tumor and patterns of spread. These are very crucial for proper treatment planning, therapy response assessment, and follow-up of patients with colorectal malignancy. Bangladesh J. Nuclear Med. 29(1): 107-110, 2026